(Transit) migration via Nepal and India: Tibetans en route to the West. (22nd November 2017) - Frilund, Rebecca
Abstract: This ethnographic study explores a novel case that has not been discussed in the context of migration theories before; migration processes and intentions of Tibetans who have migrated via Nepal to Dharamsala, India, and often intend to, or manage to, migrate onwards. It builds upon the concept of transit migration, the most established concept used to describe dynamic migration via one place or several towards migrants' possible final destinations. This type of migration has been studied mostly in Europe and its border areas, and it has been argued that the concept should only be used in this geographical area. This study challenges this claim by examining its application in the context of Tibetan migration via Nepal to India and further. Since some contested determinants of transit migration, such as initial intentions to migrate onwards and time spent in a transit spot are also discussed, the paper contributes to the scholarly debates on the possibilities and limitations of the concept. It argues that the migration of the Tibetans can be considered transit migration when they migrate via Nepal to India, whereas their migration processes and intentions to move onwards from India are much more heterogeneous in general, although some participate in transit related activities also in Dharamsala.